Identification and characterization of invasive multi-drug-resistant (MDR) Bacteroides genomospecies in Canada. Issue 5 (26th February 2020) - Graham, Christopher; Eshaghi, Alireza; Sarabia, Alicia; Zittermann, Sandra; Stapleton, Patrick; Kus, Julianne V.; Patel, Samir N.
Abstract : We identified and characterized a genome of the multi-drug-resistant Bacteroides genomospecies recovered from an invasive specimen from a hospitalized patient in Canada. The strain was resistant to penicillin, pipercillin-tazobactam, meropenem, clindaymycin and metronidazole. The strain harboured a plasmid containing the nimE gene, which has been shown to be associated with metronidazole resistance. The study highlights the importance of being vigilant in suspecting antimicrobial drug resistance when a patient is not improving on therapy.